Analisis Strategi Pemasaran Untuk Meningkatkan Daya Saing UMKM Keripik Gedebok Pisang di Blora - Octavia, Ayu Nurafni; Septiyani, Indah; Anggraini, Ida Ayu; Mayasari, Dela Anggun (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study was to determine marketing strategies in increasing the competitiveness of MSME actors, especially in the Gedebok Banana Chips business in Blora City. The analytical method uses descriptive research methods with a qualitative approach which is carried out through observation, interviews, and documentation. The results of the study show that Gedebok Pisang Chips SMEs use a marketing strategy through E-commerce, so that their product sales and skills can increase. From the analysis conducted on the product of the banana gedebok chips industry, a marketing strategy can be applied which can be used as an effort to increase competitiveness. In addition, business actors Gedebok Banana Chips also use marketing-mix. In this case, it shows that the products being sold are very attractive because the main ingredients are banana gedebok and a comfortable, clean and hygienic place, relatively cheap and affordable prices and promotions by utilizing social media such as Facebook, Instagram and WhatsApp